PENANGANAN TINDAK PIDANA PENYALAHGUNA NARKOTIKA DALAM PERSPEKTIF RESTORATIVE JUSTICE - Azkha Aflahiyah; Syarifuddin Syarifuddin; Fathorrahman Fathorrahman (HUKMY : Jurnal Hukum, 2026)
Narcotics abuse is a criminal offense in Indonesia that is still predominantly addressed through a repressive legal approach, without clear distinction between users and traffickers. In practice, many narcotics abusers, who are essentially victims of addiction, are sentenced to imprisonment without consideration for rehabilitation alternatives. This study aims to examine the application of the restorative justice concept in handling narcotics abusers in Indonesia and to assess its effectiveness as an alternative to imprisonment. This research employs a normative juridical method with a statutory approach and a case study of Denpasar District Court Decision Number 1030/Pid.Sus/2024/PN Dps. The findings indicate that, normatively, the application of restorative justice for narcotics abusers has a legal basis through Law Number 35 of 2009, the Indonesian Attorney General’s Regulation Number 15 of 2020, and the Indonesian National Police Regulation Number 8 of 2021. However, its implementation in practice remains suboptimal due to the absence of integrated assessment requests, the persistence of retributive legal paradigms, and limited inter-agency coordination among law enforcement institutions. Therefore, legal policy reform oriented toward the recovery of abusers through systematic rehabilitative and restorative approaches is urgently needed.